Globalisolationism and Its Implications for TNCs’ Global Responsibility - Frederick Ahen (Springer, 2022)
The complex structure of the tragic aspects of globalization has been accounted for in extant literature. What remains unclear is how deglobalization, isolationism and all the radically disruptive movements and politics in-between will shape transnational corporations’ (TNCs) organizational practices. The purpose of this study is to interrogate and problematize the implications of anarchic ‘globalisolationism’ vis-à-vis the atlas of insurrection and the TNCs’ global responsibility towards human-centric management
practices. We situate our analysis in the heavily politicized and contested discursive space of emergent global geopolitical and environmental tensions and the global quest to reclaim dignity, freedoms, right to resources and decisions—stakeownership.‘Globalisolationism’ is conceptualized as a radically non-compromising coexistence of globalization and isolationism by design, aided by new information technologies, reactivated mass consciousness and slack political resources. It is characterized by the
radical pursuit of new deals within the global geopolitical and economic order; renegotiation of existing deals for resource appropriation and democratic space for the marginalized; the collapse of the old political order via auto-implosion as a beneficial constraint; and the defence of the status quo in global resource and environmental governance due to ‘translocal’ insurrection. Therefore, the paper suggests how TNCs’ current modus operandi could be transformed into responsible human/environment-centric organisational practices to accommodate emerging sociopolitical and environmental challenges. It further highlights the implications for novel game-changing policies and political action by ‘subaltern’ societies and their metamorphosis from victims of planetary vandalism to stakeowners with sovereignty over their resources.
Keywords Globalization . Global sustainability. Human-centric world order . International
development order . TNCs